2021
DOI: 10.1002/pld3.307
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent increase in α‐tocopherol and phytosterols in maize leaves exposed to elevated ozone pollution

Abstract: Tropospheric ozone is a major air pollutant that significantly damages crop production. Crop metabolic responses to rising chronic ozone stress have not been well studied in the field, especially in C 4 crops. In this study, we investigated the metabolomic profile of leaves from two diverse maize ( Zea mays ) inbred lines and the hybrid cross during exposure to season‐long elevated ozone (~100 nl L −1 ) in the field using free air concentrati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…In addition, antioxidants in the apoplast, including ascorbate, glutathione, and phenolic compounds, directly scavenge ROS (Ainsworth, 2017;Grace & Logan, 2000;Wedow et al, 2021a). However, previous studies have failed to demonstrate a clear pattern of correlation between O 3 sensitivity and antioxidant compound levels among diverse species (Betzelberger et al, 2010;Choquette et al, 2020;Li et al, 2016;Wedow et al, 2021b). Furthermore, variation in plant responses to O 3 may also be partly explained by genetic background (Choquette et al, 2019;Sorgini et al, 2019).…”
Section: What Factors Influence O 3 Sensitivity Among Species?mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, antioxidants in the apoplast, including ascorbate, glutathione, and phenolic compounds, directly scavenge ROS (Ainsworth, 2017;Grace & Logan, 2000;Wedow et al, 2021a). However, previous studies have failed to demonstrate a clear pattern of correlation between O 3 sensitivity and antioxidant compound levels among diverse species (Betzelberger et al, 2010;Choquette et al, 2020;Li et al, 2016;Wedow et al, 2021b). Furthermore, variation in plant responses to O 3 may also be partly explained by genetic background (Choquette et al, 2019;Sorgini et al, 2019).…”
Section: What Factors Influence O 3 Sensitivity Among Species?mentioning
confidence: 99%
“…This further suggests that C 4 crops may have lower stomatal O 3 uptake than C 3 crops. Nevertheless, previous studies have shown significant impacts of O 3 on maize ( Zea mays ) (Choquette et al, 2019 , 2020 ; Sorgini et al, 2019 ; Wedow et al, 2021b ; Yendrek et al, 2017a , 2017b ), switchgrass ( Panicum virgatum ) (Li et al, 2019 ) and sugarcane (Saccharum spp.) (Moura et al, 2018 ), but not on sorghum ( Sorghum bicolor L.) (Li et al, 2021 ) under field conditions, implying the adverse effects of O 3 on plant photosynthesis and productivity vary among C 4 species and genotypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, only four C 4 crops have been studied for O 3 response using O 3 ‐FACE facilities (Table 1 ). Research from SoyFACE showed elevated O 3 concentrations (approximately 100 ppb) significantly reduced leaf photosynthetic capacity in maize (Choquette et al., 2019 , 2020 ; Sorgini et al., 2019 ; Wedow et al., 2021b ; Yendrek et al., 2017a , b ), but had little or no effect on photosynthesis and biomass yield in switchgrass (Li et al., 2019a ) and sorghum (Li et al., 2021 ). These studies also reported considerable genotypic variation in O 3 sensitivity among maize and sorghum lines (Choquette et al., 2019 ; Li et al., 2021 ; Yendrek et al., 2017a , b ).…”
Section: Lessons Learned From Face Experimentsmentioning
confidence: 99%
“…Wedow et al. ( 2021b ) investigated differential sensitivity between two inbred maize lines (B73 and Mo17) and the hybrid cross (B73 x Mo17) in relation to the accumulation of defense metabolites in leaf tissue. Senescence was accelerated in the hybrid compared to the inbred lines under elevated [O 3 ] and O 3 ‐induced reductions in photosynthetic carbon assimilation during grain filling were greater in the hybrid line, leading to significantly greater yield loss.…”
Section: Lessons Learned From Face Experimentsmentioning
confidence: 99%